An evaluative study of the role of United States information service libraries in the Philippines - Adler, Alice Cecilia 1923- (1969)
In order to carry out these objectives, they provide free public library service available to everyone, and also try to reach special audiences with specialized collections. Because of shifting patterns of power and the high rate of literacy and education which broaden the base of potential leadership, it is important not to neglect the mass audience while making special efforts to reach small groups of opinion leaders.